Assessment of the Ductus Arteriosus in Fetuses with Tetralogy of Fallot and the Implication for Postnatal Management. (26th December 2013) - Tuo, Giulia; Volpe, Paolo; Buffi, Davide; De Robertis, Valentina; Marasini, Maurizio
Abstract Objective To describe the antenatal and neonatal echocardiographic morphology and flow pattern of the ductus arteriosus in patients with tetralogy of Fallot. Patients and Methods We included patients with a prenatal diagnosis of tetralogy of Fallot between January 2006 and December 2012. Results Among the 52 fetuses with tetralogy of Fallot the severity of right ventricular outflow obstruction was considered mild in 32, moderate in 14, and severe in 6. In the mild right ventricular outflow obstruction group (n = 32) all had normal ductal morphology and flow pattern, eight (25%) elected for termination of pregnancy and two died in the neonatal period from extracardiac causes. In the moderate right ventricular outflow obstruction group (n = 14) the fetuses had a small ductus arteriosus with antegrade but abnormal flow velocity, one (7%) elected for termination of pregnancy. Immediately after birth the ductus arteriosus was very small or already closed at echocardiographic examination. Two out of 13 patients (15%) developed severe hypoxic spells and underwent modified Blalock–Taussig shunt during the neonatal period. Six fetuses were considered to have severe right ventricular outflow obstruction with flow reversal in the ductus arteriosus, three (50%) of whom elected for termination of pregnancy. The other three newborns underwent modified Blalock–Taussig shunt. Conclusion In fetuses with tetralogy of Fallot, ductal diameter can be reduced even up to prenatal closure. Prenatal ductal morphology assessment may be useful for improving management of patients with moderate right ventricular outflow obstruction and small ductus arteriosus who may become cyanotic at birth.